2016
DOI: 10.1080/10256016.2016.1186671
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of snow and glacier melt contribution to Liddar stream in a mountainous catchment, western Himalaya: an isotopic approach

Abstract: Snow- and glacier-dominated catchments in the Himalayas are important sources of fresh water to more than one billion people. However, the contribution of snowmelt and glacier melt to stream flow remains largely unquantified in most parts of the Himalayas. We used environmental isotopes and geochemical tracers to determine the source water and flow paths of stream flow draining the snow- and glacier-dominated mountainous catchment of the western Himalaya. The study suggested that the stream flow in the spring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 28 publications
3
26
2
Order By: Relevance
“…It is more difficult to compare our computed fractions of glacier melt in stream water with estimates in other sites because they can be highly dependent on the yearly climatic variability, on the proportion of glacierized area in the catchment and because they are usually reported at the monthly or yearly scale. However, when considering the total meltwater contribution, the computed fractions for the June-August period agree reasonably well with those recently estimated at the seasonal scale in other high-elevation catchments by Pu et al (2013) (41-62, 12 % of glacierized area), Fan et al (2015) (26-69 %), Xing et al (2015) (almost 60 %) and at the annual scale by Jeelani et al (2016) (52, 3 % of glacierized area), and are even higher than those computed by Mukhopadhyay and Khan (2015) (25-36 %). These observations stress the importance of water resources stored within the cryosphere even in catchments with limited extent of glacierized area, such as the Saldur catchment.…”
Section: Role Of Snowmelt and Glacier Melt On Streamflowsupporting
confidence: 75%
See 1 more Smart Citation
“…It is more difficult to compare our computed fractions of glacier melt in stream water with estimates in other sites because they can be highly dependent on the yearly climatic variability, on the proportion of glacierized area in the catchment and because they are usually reported at the monthly or yearly scale. However, when considering the total meltwater contribution, the computed fractions for the June-August period agree reasonably well with those recently estimated at the seasonal scale in other high-elevation catchments by Pu et al (2013) (41-62, 12 % of glacierized area), Fan et al (2015) (26-69 %), Xing et al (2015) (almost 60 %) and at the annual scale by Jeelani et al (2016) (52, 3 % of glacierized area), and are even higher than those computed by Mukhopadhyay and Khan (2015) (25-36 %). These observations stress the importance of water resources stored within the cryosphere even in catchments with limited extent of glacierized area, such as the Saldur catchment.…”
Section: Role Of Snowmelt and Glacier Melt On Streamflowsupporting
confidence: 75%
“…The spatial and temporal variability of an end-member tracer signal is usually very difficult to characterize at the catchment scale (Hoeg et al, 2000), especially in glacierized catchments (Jeelani et al, 2016), and it can noticeably affect the uncertainty of the results of mixing models. Since field measurements cannot reliably capture such a large spatial and temporal variability, we identified four different scenarios of mixing model application, assuming that they were representative for this variability.…”
Section: Scenarios Of Mixing Model Applicationmentioning
confidence: 99%
“…These became progressively lower with a minimum at 15:30 (CET) in the afternoon when the melt rate was highest. Jeelani et al () found higher EC values in meltwater originating from a debris‐covered glacier compared with a clean glacier. Because glacier melt tracer signatures depend on the water origin (e.g., supraglacial meltwater vs. glacier outflow), the origin of the air masses that form precipitation and the post‐depositional processes, a direct comparison is solely valuable for catchments with similar climate conditions and physical characteristics.…”
Section: Discussionmentioning
confidence: 98%
“…A novel approach for obtaining snowmelt water samples for isotope analysis was presented including the strengths and weaknesses of proposed PCS method in comparison to other techniques. In each participating country, the PCSs were deployed according to its own specific research questions and requirements (Jeelani et al, 2016;Krajči et al, 2016;Massone et al, 2016;N'da et al, 2016;Penna et al, 2014Penna et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%